Biomass and Neutral Lipid Production in Geothermal Microalgal Consortia - Bywaters, Kathryn F.; Fritsen, Christian H. (Frontiers in Bioengineering and Biotechnology, 2015)
Recently, technologies have been developed that offer the possibility of using algal biomass as feedstocks to energy producing systems – in addition to oil-derived fuels (Bird et al., 2011, 2012). Growing native mixed microalgal consortia for biomass in association with geothermal resources has the potential to mitigate negative impacts of seasonally low temperatures on biomass production systems as well as mitigate some of the challenges associated with growing unialgal strains. We assessed community composition, growth rates, biomass, and neutral lipid production of microalgal consortia obtained from geothermal hot springs in the Great Basin/Nevada area that were cultured under different thermal and light conditions. Biomass production rates ranged from 39.0 to 344.1 mg C L−1 day−1. The neutral lipid production in these consortia with and without shifts to lower temperatures and additions of bicarbonate (both environmental parameters that have been shown to enhance neutral lipid production) ranged from 0 to 38.74 mg free fatty acids (FFA) and triacylglycerols (TAG) L−1 day−1; the upper value was approximately 6% of the biomass produced. The higher lipid values were most likely due to the presence of Achnanthidium sp. Palmitic and stearic acids were the dominant free fatty acids. The S/U ratio (the saturated to unsaturated FA ratio) decreased for cultures shifted from their original temperature to 15°C. Biomass production was within the upper limits of those reported for individual strains, and production of neutral lipids was increased with secondary treatment. All results demonstrate a potential of culturing and manipulating resultant microalgal consortia for biomass-based energy production and perhaps even for biofuels.